2017
DOI: 10.4187/respcare.05280
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pulmonary Arterial Hypertension Using Initial Combination Therapy of Bosentan and Iloprost

Abstract: Initial combination therapy in treatment-naive PAH subjects with WHO functional class III or IV can significantly improve 6MWD, hemodynamics, and quality of life compared with monotherapy. Further studies with large samples and placebo controls are required to assess the tolerability and efficacy of initial combination therapy in patients with PAH. (ClinicalTrials.gov registration NCT01712997).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
(26 reference statements)
0
11
0
1
Order By: Relevance
“…The New York Heart Association (NYHA) and the World Health Organization (WHO) functional classification systems were used to identify functional impairment in PAH. McLaughlin et al (33) and Hoeper et al (34) performed their studies using the NYHA functional classification, the remaining three studies were performed using the WHO functional classification (23,35,36). After meta-analysis, the result showed that there was significant heterogeneity (I 2 =73%; P=0.02) in WHO functional class improvement I between bosentan combination therapy and bosentan monotherapy (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The New York Heart Association (NYHA) and the World Health Organization (WHO) functional classification systems were used to identify functional impairment in PAH. McLaughlin et al (33) and Hoeper et al (34) performed their studies using the NYHA functional classification, the remaining three studies were performed using the WHO functional classification (23,35,36). After meta-analysis, the result showed that there was significant heterogeneity (I 2 =73%; P=0.02) in WHO functional class improvement I between bosentan combination therapy and bosentan monotherapy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the five trial studies reported the effects of bosentan combination therapy on mean PAP (mPAP; Fig. 5) (33,35). The difference of mPAP demonstrated an average of only 11.95 mmHg (95% CI: −17.06, −6.83; P<0.00001) between bosentan combination therapy and monotherapy, and there was no heterogeneity between the groups (I 2 =6%; P=0.30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the initial combination therapy, it was confirmed for the first time that the WHO FC II–III PAH patients received combination therapy more benefits in the Research of AMBITION in 2015 (Galiè et al, 2015 ). Since then, more and more evidence, including large RCTs, supports initial combination therapy as an effective treatment strategy for PAH (Hassoun et al, 2015 ; Han et al, 2017 ; D’Alto et al, 2018 ). Therefore, the 2018 WORLD SYMPOSIUM ON PULMONARY HYPERTENSION (WSPH) emphasized the importance of combination therapy for PAH patients and recommended low/intermediate/high-risk PAH patients with negative acute vascular reactivity test should first consider the combination of ERA and PDE5i (Qin and Zhi-Hong, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Еще [40,41]. В многоцентровом открытом РКИ III фазы X. Han и соавт., 2017 (n=27) [42] у больных ЛАГ III-IV ФК продемонстрировали, что стартовая комбинация бозентана и ингаляционного илопроста эффективнее увеличивала дистанцию 6МХ, улучшала показатели гемодинамики (среднее ДЛА, сердечный индекс), NT-proBNP, ФК и качество жизни по сравнению с монотерапией каждым из препаратов. Лекарственного взаимодействия между ингаляционным илопростом и бозентаном не отмечается [43].…”
unclassified